2015
DOI: 10.1007/s10452-015-9501-z
|View full text |Cite
|
Sign up to set email alerts
|

Fish reduce habitat coupling by a waterbird: evidence from combined stable isotope and conventional dietary approaches

Abstract: Aquatic consumers can function as habitat couplers by using allochthonous subsidies of prey that migrate across ecosystem boundaries. We examined the relative use of allochthonous (invertebratesterrestrial or living on littoral vegetation; immigrating amphibians) versus autochthonous (aquatic invertebrates, fish) resources by the red-necked grebe Podiceps grisegena, a generalist predator, on fishless ponds versus ponds stocked with common carp Cyprinus carpio. We combined conventional methods of diet estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Earlier research on the trophic ecology of Red-necked Grebes (the North American subspecies Podiceps grisegena holboellii) on boreal lakes in Canada suggested that females incorporated locally derived nutrients into eggs (Paszkowski et al 2004). Our previous study on exploitation of local resources by grebes, using yolks from eggs collected mainly in mid-season, led to basically the same conclusion (Kloskowski and Trembaczowski 2015). Here we used eggs laid early in the season.…”
Section: Nutrient Transfer and Allocation To Eggsmentioning
confidence: 70%
See 3 more Smart Citations
“…Earlier research on the trophic ecology of Red-necked Grebes (the North American subspecies Podiceps grisegena holboellii) on boreal lakes in Canada suggested that females incorporated locally derived nutrients into eggs (Paszkowski et al 2004). Our previous study on exploitation of local resources by grebes, using yolks from eggs collected mainly in mid-season, led to basically the same conclusion (Kloskowski and Trembaczowski 2015). Here we used eggs laid early in the season.…”
Section: Nutrient Transfer and Allocation To Eggsmentioning
confidence: 70%
“…Interannual differences in the location of wintering grounds and diet composition may have affected the results (cf. Hobson et al 2011), but on the breeding grounds food sources were determined by pond culture regime and did not vary isotopically between years (Kloskowski and Trembaczowski 2015). Sample sizes also differed between analyses, mainly because of the varying amount of material for isotopic assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were combined across years due to low sample sizes within each year. We assumed that given pond management procedures, including regular pond drainage and refilling, isotopic signatures of primary producers that supported the pond food webs did not change significantly over the study period (Kloskowski and Trembaczowski 2015).…”
Section: Stable Isotope Analysesmentioning
confidence: 99%